Exploring hydrodynamic cavitation for citrus waste valorisation in Malta: from beverage enhancement to potato sprouting suppression and water remediation - Psakis, Georgios; Lia, Frederick; Valdramidis, Vasilis P.; Gatt, Ruben (Frontiers in Chemistry, 2024)
The endorsement of circular economy, zero-waste, and sustainable-development strategies by the European Union and the United Nations, has encouraged the adoption of non-thermal technologies in both the agro-food and health industries. Whilst integration of such technologies in the processing pipelines of northern European countries has been progressing in fast paces, pathways for their implementation in the food-supply chains of the Mediterranean region appear uncertain or undefined. Considering the fresh orange juice supply chain of the Maltese Islands, we have bench-scale assessed the effectiveness of hydrodynamic cavitation in bioactive compound extraction from the collected peel of squeezed Navel and Valencia oranges (Citrus sinensis) in water and 70% (v/v) ethanol. Brief hydrodynamic cavitation treatments of dried peel in water (35 o C) achieved extraction of bioactive compounds surpassing conventional macerations, whereas prolonged cavitation in 70% ethanol (-10 o C), preserved the nature of bioactive flavonoids and enhanced H2O2 scavenging. Cavitationally treated peel exhibited potato sprouting suppression propensity, as well as favourable adsorption capacity for Cu 2+ , nitrates and nitrites. Hereby, we provide a perspective on the possible integration of hydrodynamic cavitation in the Maltese food-supply chains and examine plausible valorisation schemes for the development of new foods as well as for water remediation.